Tailoring in the digital era: Stimulating dialogues on health topics in collaboration with social media influencers. (January 2019) - Lutkenhaus, Roel O; Jansz, Jeroen; Bouman, Martine PA
In today's media landscape, audiences increasingly turn to online communities for media consumption and to exchange information about specific niche interests such as health-related topics. This calls for a segmented approach in which interventions are targeted at online communities, tailored to their specific cultures and health-related perceptions, and leverage the dynamics of conversation and social influence in online networks. Strategies drawn from the field of influencer marketing provide interesting opportunities to reach and engage with audiences in a personally relevant manner, including with those who may disagree with an intervention's message. This article reflects on what health communicators might learn from influencer strategies and proposes digital methods to target and tailor health communication in the digital era. More concretely, we present methods to: (a) identify online communities engaging on a specific health issue; (b) map community specific cultures and health-related perceptions; and (c) identify influencers as potential collaboration partners. As such, we adopt a slightly different take on tailoring by putting the creative and cultural competences of social influencers central, and by aligning our methods with a media mapping protocol to create influencer strategies that are tailored to the cultures and health-related perceptions of multiple online audience segments. We illustrate the potential of these methods with a study of how vaccination is discussed among Dutch Twitter users.